Serum α-KL, a potential early marker of diabetes complications in youth with T1D, is regulated by miRNA 192 - Gong, Zhenwei; Banchs, Pedro A. Pagán; Liu, Ye; Fu, Haoyi; Arena, Vincent C.; Forno, Erick; Libman, Ingrid; Ho, Jacqueline; Muzumdar, Radhika (Frontiers in Endocrinology, 2022)
Despite the wealth of information on biomarkers of diabetes complications in adults with type 1 diabetes, data in the pediatric population is limited. Diabetic nephropathy (DN), the leading cause of mortality in type 1 diabetes T1D), could be potentially missed in youth, as albuminuria, the current “gold” standard, may be transient and may not reflect permanent renal impairment. Soluble alpha klotho has emerged as a potential marker of early diabetic nephropathy. Seventy-nine pediatric patients with type 1 diabetes meeting ISPAD criteria for nephropathy screening were consecutively recruited (90% Caucasian, 51% male, mean age 16.1±3.1 years, duration of T1D 7.2±3.9 years, 2-year average HbA1c 8.0±1.3%), and serum and urine samples were collected for analysis. Serum klotho (KL) and circulating miRNA levels of select miRNA involved in the pathogenesis of DN were estimated. KL had a strong inverse correlation with diabetes duration and HbA1c, important risk factors in development of diabetes complications. Serum miR-192 were negatively associated with KL among children with prolonged duration of diabetes (≥12 years) after adjustment for age and sex. In cell culture, overexpression of miR-192 significantly downregulated KL mRNA and protein levels and reduced KL levels in the media. miR-192 mimic reduced luciferase activity in a reporter containing the KL 3' UTR (60% compared to controls, p<0.01), and the inhibitor rescued it. Deletion of a potential binding site for miR-192 in the KL 3’UTR completely abolished the effect of miR-192 in the reporter assay, suggesting that KL is a direct target gene of miR-192. Overexpression of miR-192 significantly increased oxidative stress (malondialdehyde, MDA) and expression of inflammatory and senescence markers IL-6 and p16. Inhibition of miR-192 reduced levels of MDA to normal. In conclusion, we demonstrate an increase in miR192 and a decrease in KL levels in children with prolonged duration of T1D. We demonstrate a novel role for miR-192 in directly regulating KL levels, and through that, senescence and oxidative stress, key pathological processes in the development of DN. miR-192 and/or KL levels are altered with severity and duration of diabetes and could serve as early biomarkers for DN.